Arabizi: a writing variety worth learning? an exploratory study of the views of foreign learners of Arabic on Arabizi. - Farrag, Mona (AUC Knowledge Fountain, 2012)
This paper investigates the views of learners of Arabic as a foreign language (AFL) on Arabizi as well as the possible effects of these views on the field of Teaching Arabic as a Foreign Language (TAFL). For purposes of this paper, Arabizi is defined as: writing Arabic in Latin characters and Arabic numerals on computer-mediated communication (CMC). The study tries to answer the following research question: What is the attitude of AFL learners on Arabizi regarding: a. its effect on their communicative skills with native Egyptians on CMC? b. learning AFL? In a pilot study, a web-based questionnaire was posted on the researcher's Facebook page and copies were handed to AFL students enrolled in the spring program in the Arabic Language Institute (ALI) at The American University in Cairo (AUC). Nineteen complete responses were received and analyzed. The questionnaire was amended for the main study and 23 responses were gathered from students enrolled in the summer course of The Center for Arabic Studies Abroad (CASA). The results of both the pilot and the main study indicate that AFL students believe that Arabizi hinders an effective communication in Arabic on CMC and complicates AFL learning process. The participants express their need to learn Arabizi in order to have better communication with Egyptians on CMC. Moreover, they think that Arabic is acquiring a new writing variety. The researcher examines the potential consequences of these views on the field of TAFL and the status of Arabic language on CMC.